Female Nurse Performance Model Based on Triple Roles Conflict and Job Stress in Pandemic COVID-19 - Komalasari, Yeyen; Krismawintari, Ni Putu Dyah; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
being a nurse is not just a matter of restoring a patient’s physical health. More than that, nurses have an obligation to provide mental support to patients in order to remain optimistic about achieving recovery. What’s more, to patients infected with COVID-19. The testimony of one of the nurses stated that he understood anyone who was infected with COVID-19 had the opportunity to experience a mental breakdown and that is where the humanist duty of a nurse was tested. The purpose of this study is to explain the performance of female nurses affected by triple roles conflict and job stress who they work at an accredited government hospital in Bali. The population in this research was married women and has children and for respondents were 52 nurses. The data analysis used regression analysis techniques. The results of this study found that triple roles conflict had a negative and significant effect on the performance of nurses. There was a negative and significant influence between job stress and performance of nurses. Also, there was a simultaneous negative influence between triple roles conflict and job stress on the performance of nurses. It can be concluded that there was an influence between triple roles conflict and job stress on women nursing performance partially or simultaneous. Therefore, female nurses, as well as housewives who have triple role conflict and job stress, are expected to have good time management that can improve aspects of their performance so be able to carry out their duties, and no one role is neglected.